IS IT SUFFERING OR CRISIS? PSYCHOLOGICAL ANALYSIS OF THE PSEUDO CRISIS EXPERIENCES - Hovhannisyan, H.R. (Modern Psychology, 2025)
This article is about life crisis and attached therms of mental suffering. The thing is that there is some confusion associated with human experiences and crises. We are making an effort to clarify the causal nexus of human life turmoils, suffering and attitudes. And we offer a descriptive model for differentiation of the crisis experiences and psychological suffering. Also we have touched upon addiction to the risk as a means of coping or blocking a personal crisis.